Interferência do polimorfismo rs9939609 do gene FTO na evolução antropométrica e metabólica após o tratamento cirúrgico da obesidade grau III - Gisele Kuhlmann Duarte Rodrigues (2015)
The rs9930609 single nucleotide polymorphism (SNP) in the fat mass and obesity associated gene (FTO) is an important polymorphism involved in obesity. Although several studies have evaluated the influence of the FTO SNP on the clinical treatment of obesity, few studies have been conducted on patients who underwent bariatric surgery. We evaluated the influence of FTO SNP on body weight, body composition, weight regain and metabolic outcomes during a 60-month follow-up period after bariatric surgery. The rs9930609 was genotyped in 165 individuals using a real-time PCR TaqMan assay. Data for life style, comorbidities, biochemical data, body weight, body mass index (BMI), excess weight loss (EWL) and body composition were obtained before and 6, 12, 18, 24, 36, 48 and 60 months after surgery. Data were analyzed by comparing two groups of patients according to the presence of rs9939609 FTO gene polymorphism and genotype. Mixed regression models wereconstructed to evaluate the dynamics of body weight, BMI and EWL over time in female patients. No differences were observed between the groups during the first 24 months after surgery. Four individualswere excluded from the sample due to the inconclusive genotype and 15 given the short time elapsed from surgery . Of the 146 individuals classified for SNP rs9939609 of FTO gene, 42 individuals (28.8%) did not have the FTO gene polymorphism (TT) , 72 (49.3%) had a risk allele(AT) and 32 (21.9%) had two risk allele (AA). The average age of the individuals was 41.84 years and the majority ( 84.9 %) were women. The data are in Hardy-Weinberg equilibrium (HWE). The allelic frequency was 70.6 % and 29.4% of subjects caring allele A and T, respectively. The minor allele frequency (MAF) observed in this study (0.465) for rs9939609 was similar to that found in dbSNP (0.340). After 36, 48 and 60 months, body weight, fat mass and BMI were higher, whereas EWL was lower in the FTO-SNP patient group. Weight regain was more frequent and occurred sooner in the FTO-SNP group. The greater weight of both body compartments (fat mass and fat free mass) justified higher bodyweight after a few years of surgery. There is a different evolution of weightloss in obese carriers of the FTO variant rs9939609 after bariatric surgery. However, this pattern was evident at only two years after surgery, inducing a lower proportion of surgery success and a greater and earlier weight regain